Taxonomia e distribuição de Dinotrema (Dinotrema) Foerster (Hymenoptera: Braconidae: Alysiinae) da Mata Atlântica (Brasil) - Oliveira, Franciélle Dias de (Universidade Federal de São Carlos, 2025)
Dinotrema Foerster (Hymenoptera: Braconidae: Alysiinae) is a large and taxonomically complex genus of endoparasitoids of Diptera, with numerous undescribed species, particularly in tropical regions. In the New World, two of its three subgenera occur: Dinotrema and Synaldis, with ca. 80% of the genus’s species included in the former. The Neotropical fauna of the subgenus Dinotrema remains poorly explored, with only seven species formally described, while many others remain unidentified in biological collections. This study is based on the morphological analysis of about 2,000 specimens of the subgenus Dinotrema deposited in the Coleção Taxômica do Departamento de Ecologia e Biologia Evolutiva da Universidade Federal de São Carlos, São Carlos, Brazil, collected from Atlantic Forest areas. Twenty-three new species are described, and specimens of three previously known species from Brazil were recorded: Dinotrema (Dinotrema) multiareolatum Peris-Felipo, D. (D.) plaumanni Peris-Felipo and D. (D.) subbidentatum Peris-Felipo. Chapter 1 addresses taxonomic descriptions, morphological variations, an identification key for Neotropical species, and a discussion of relevant morphological characters. Chapter 2 details the distribution and occurrence of the specimens: 1,756 specimens were assigned to species, with records from seven states and 27 municipalities in the South and Southern regions of Brazil. Approximately 90% of the specimens were collected in protected areas, encompassing 19 conservation units. Some species, such as D. (D.) sp. nov. 1, D. (D.) multiareolatum, and D. (D.) plaumanni, exhibited broad distributions, with numerous specimens recorded, while others occurred in smaller numbers, with four species recorded exclusively in a single conservation unit each. This study expands knowledge on the taxonomy and distribution of the subgenus in the Neotropical region, highlighting the importance of biodiversity research, the conservation of natural areas, and biological collections.
Taxonomy and distribution of Dinotrema (Dinotrema) Foerster (Hymenoptera: Braconidae: Alysiinae) from the Atlantic Forest (Brazil)
Taxonomía y distribución de Dinotrema (Dinotrema) Foerster (Hymenoptera: Braconidae: Alysiinae) de la Mata Atlántica (Brasil)
Keywords: Alysiini; Endoparasitoide cenobionte; Ichneumonoidea; Grupo Aspilota; Região Neotropical; Padrões de distribuição; Taxonomia alfa; CIENCIAS BIOLOGICAS::ZOOLOGIA::TAXONOMIA DOS GRUPOS RECENTES; CIENCIAS BIOLOGICAS::ZOOLOGIA; CIENCIAS BIOLOGICAS::ECOLOGIA